Biometric indices and population parameters of three polynemid fishes from Batang Lassa Estuary of East Malaysia - Mustafa, M. Golam; Amy Halimah, Rajaee; Hadi, Hamli; Khairul Adha, A. Rahim (2021)
The length-weight relationships (LWRs), condition factor (Kn), growth, mortality and exploitation status of three polynemid fishes, i.e., Filimanus xanthonema (Valenciennes, 1831), Polynemus melanochir (Valenciennes, 1831) and Polynemus paradiseus (Linnaeus, 1758) from Batang Lassa River estuary were estimated. Fish samples were caught during April 2019 to September 2020 using the ESBN (locally called Gnian) having 1.25 to 4.00 cm mesh size. The total length (TL) and body weight of each individual fish was measured to the nearest 0.1 cm and 0.01 g respectively. The growth coefficients (b) for F. xanthonema, P. melanochir and P. paradiseus, were 2.880, 2.717 and 2.724 with the R2 values 0.956, 0.972 and 0.936 respectively. Estimated growth coefficients indicated a negative allometric growth pattern for all three threadfin fishes. To date, information regarding length-weight relationships for F. xanthonema and P. melanochir is insufficient whereas the information is available for P. paradiseus. About 40–48% of fishes exhibited flat or thin body shape (Kn < 1), 48–50% were rounded or fat (Kn > 1) and only 1–3% of fishes showed proportional body shape (Kn = 1). The growth parameters L∞, K and ϕ’ were estimated at 15.75 cm, 0.95 yr−1 and 2.37 for F. xanthonema; 27.61 cm 0.87 yr−1 and 2.82 for P. melanochir; and 27.30 cm, 0.58 yr−1 and 2.64 for P. paradiseus; respectively. The estimated natural mortality (M) included 2.10, 1.69 and 1.30 yr−1 ; the fishing mortality (F) 0.57, 0.67 and 0.60 yr−1 ; and exploitation ratio (E) 0.21, 0.28 and 0.31 for F. xanthonema, P. melanochir and P. paradiseus respectively. The study concluded that the stocks are still under exploitation (E < 0.5) condition. However, the studied Batang Lassa estuary could be a potential nursery ground considering the minimum lengths of 5.0, 3.8 and 4.0 cm for F. xanthonema, P. melanochir and P. paradiseus respectively. Therefore, management initiatives are needed to escape juvenile catches.